Stroke - Dehkharghani, Seena (Exon Publications, 2021)
Stroke remains a global risk to public health, and a pernicious source of mortality and loss of independence in those afflicted. The preceding decade has seen the transformation of the stroke management landscape, with disruptive diagnostic, therapeutic, prognostic, and rehabilitative strategies rapidly introduced to the armament of clinical and basic stroke neuroscience providers and investigators. This book offers a unique view of this condition-a human condition which knows no geographic boundaries and continues to draw the attention of an indefatigable community of physicians, scientists, engineers, nurses, and allied care personnel-synthesizing the latest among contemporary philosophies regarding the care of such patients. The authors touch upon several critical aspects of stroke care, such as diagnosis (neuroimaging in perinatal, pediatric, and adult populations), clinical care (approach to stroke in young adults, surgical treatments for stroke, and prevention of non-cardioembolic stroke), stroke related complications (memory impairment and unilateral spatial neglect), as well as stroke in the setting of the novel sars-cov-2 virus. As such, this book is of tremendous value to a wide audience seeking information on challenges in stroke care faced by clinical providers and highlights potential areas of research for stroke researchers.